Analisis Kualitatif Deskriptif Terhadap Integrasi AI Dalam Kurikulum PAI Pasca Kurikulum Merdeka - Deden, Deden (Prgram Studi Pendidikan Agama Islam, 2025)
This study analyzes the integration of artificial intelligence (AI) in the Islamic Religious Education (PAI) curriculum in the post-implementation context of the Independent Curriculum at MTs Sunanul Huda Natar. The research background is based on the urgency of utilizing digital technology in religious learning to improve literacy competencies, creativity, and personalized student learning. This study aims to describe the form of AI integration in PAI learning, identify supporting and inhibiting factors, and explain the level of madrasah readiness in adapting technology-based curriculum innovations. The study used a qualitative descriptive approach through interviews, observations, and documentation. The results show that the use of AI in PAI learning has been carried out in the preparation of materials, assessment development, and provision of learning enrichment, but its application is still limited to simple features. Teacher competency factors, the availability of technological facilities, and policies have a significant influence on the level of AI integration. The study concludes that AI integration has great potential to improve the quality of PAI learning, but still requires further training, technical assistance, and more operational policy arrangements.